Do you want to be told if you have cancer? A cross-sectional survey of Ghanaians - Elliot A. Asare; Alisha Lussiez; Melissa H. Watt; Charles K. Dally; Eileen A. Micah; Gifty Kwakye (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Not much is known about the information preferences of individuals at risk for cancer in sub-Saharan Africa. Clinicians exercise great autonomy in how, when, and to whom they disclose patients' medical diagnosis and prognostic status. We sought to investigate the information preferences with regards to cancer diagnosis and prognosis of a cross-section of Ghanaians living in and outside of Ghana. # Methods We surveyed a general population of Ghanaians aged ≥ 18 years old, living in and outside of Ghana about their cancer information preferences. Survey questions were developed using Qualtrics software and deployed via WhatsApp mobile app. After initial pilot to assess for feasibility and cultural relevance, initial links were distributed through social and medical contacts who were then asked to share widely with their social contacts. Participant characteristics were reviewed and their association with cancer information needs evaluated with logistic regression analysis. # Results Of the four hundred and twenty-six participants who responded to the survey, 33.1% were female. Majority of respondents (81.9%) were living in Ghana at time of survey. Four hundred and twelve (96.7%) patients would like to know from their provider if they were diagnosed with cancer. The most common information need of participants was treatability/curability (92%) of the cancer. A worry about impact of cancer on family was the most common reason for not wanting any information. Univariate analysis did not identify any factors associated with reduced cancer information needs. # Conclusions The overwhelming majority of Ghanaians surveyed would like to know if they were diagnosed with cancer. It is imperative that clinicians tell Ghanaians about their cancer diagnosis and share all pertinent information with them.